Characterization of the Angico dos Dias alkaline-carbonatite complex for phosphate rock processing - Carlos Eduardo Domingues da Mata; Carlos Alberto Pereira; André Carlos Silva; Pedro Lucas Rodrigues de Sousa (Journal of Materials Research and Technology, 2020)
The alkaline-carbonatite complex of Angico dos Dias, located in the Northeast of Brazil, is currently exploited to produce phosphate rock concentrate. Coarse particles (above 600 µm) are processed through a dry route accounting for 53% of the run of mine. Chemical and mineralogical compositions, density, particle size distribution, mineralogical associations, and mineral liberation were determined. A wet processing route for the fine particles was proposed in this paper, comprehending the following stages: scrubbing, low-intensity magnetic separation, desliming, milling, anionic direct flotation, and wet high-intensity magnetic separation. X-ray diffraction analysis showed fluorapatite as the main phosphate bearing mineral, silicates and iron oxyhydroxides are the predominantly gangue minerals. Mineral liberation analysis showed that 40.8% of the apatite particles had completely exposed surface and 73.05% had at least 90%. Regarding mineral liberation, 87.6% were entirely liberated and 11.6% were binary association. Energy dispersive spectrum microanalysis results showed the presence of three rare earth elements bearing minerals in the ore. The average P2O5 content of the ROM ore was 15.39%, and its recovery above 212 µm was 76.95%. Below this size, the P2O5 content decrease progressively, whereas the Fe2O3, Al2O3, and SiO2 contaminants increase. The absence of calcite and dolomite could favor the process selectivity in an anionic direct flotation using fatty acids as collectors. Therefore, the proposal for a wet processing design for concentration of apatite covers.